Criteria and indicators for assessing the level of formation of a noble attitude towards women in adolescents - Kokhan, Diana (ScienceRise: Pedagogical Education, 2020)
Based on the lack of research, but the relevance of the topic of modern society, the study identifies and theoretically substantiates the criteria for the formation of a noble attitude and their respective indicators. The purpose of the study was to characterize the specific criteria and indicators of the formation of this attitude in adolescents on the basis of different approaches to the problem of the study. Based on the analysis of psychological and pedagogical literature, the concept of "criterion" was clarified, which we understand as certain features that check the formation of a noble attitude towards women and analyze the dynamics of development, and the concept of "indicator", the formation of this concept for each of the criteria. Given that moral education includes a noble attitude towards women, analyzed a number of works by scientists to determine the general level of moral education, identified the criteria and indicators that characterize the concept, namely: cognitive-behavioral (characterized by completeness and depth of knowledge about the features of manifestation of a noble attitude and application of this knowledge in practice in everyday life), volitional (characterized by the formation of motives that will motivate the individual to selfless actions in accordance with the laws of ethics and morality, and meeting the needs of the individual, as well as experiencing certain emotions and feelings to representatives of the opposite sex), the person-reflexive (includes the nature of the identification of noble qualities of personality, accompanied by a desire to become even better). The defined criteria and indicators make it possible to assess the level of formation of noble attitudes in adolescents and analyze the dynamics of their changes during the experiment. The prospect of further scientific research is to study the dynamics of changes in the level of formation of a noble attitude in accordance with certain criteria and indicators with the help of selected diagnostic tools.